Biology and Economics: Metaphors that Economists usually take from Biology (2020)
Adam Smith, Alfred Marshall, Stanley Jevons, Karl Marx, Francois Quesnay and Joseph Schumpeter all have at least one thing in common: they used biological metaphors when speaking about economics. Nonetheless, today, this relation subsists and biology and economics are viewed as complementary sciences that have a lot to gain from joint research in fields like: evolutionary economics, economic growth, cognitive economics and environmental and ecological economics, among others. This paper, divided in four sections, will show this conclusion and explain that biology and economics are more sisters than strangers